Methodological aspects of the problem of measuring shadow activity in the economy - M. D. Khabib; N. A. Abroskina (Вестник университета)
The relevance of the problem of measuring shadow activity and its significance for the purposes of macroeconomic analysis and forecasting is emphasized. The importance of forming an adequate methodological base for measuring shadow activity and developing an information support system for its research is substantiated. The existing approaches to the definition of shadow activity and methods of its measurement are analyzed. The possibility of building an information base and obtaining appropriate estimates of shadow activity on the basis of resource and use tables developed at the national level is evaluated. The possibility of using the resource approach as the most objective method of reflecting the volume and components of shadow activity at the sectoral and macro levels is studied. The conditions for the use of the resource approach are determined, taking into account the specifics of the industry features of the formation of output and intermediate consumption indicators. The possibility of constructing dynamic series of indicators constructed using the resource approach for analytical purposes is evaluated.